2015
DOI: 10.1094/mpmi-06-15-0141-r
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobial Diversity and Nodulation Characteristics of the Extremely Promiscuous Legume Sophora flavescens

Abstract: In present study, we report our extensive survey on the diversity and biogeography of rhizobia associated with Sophora flavescens, a sophocarpidine (matrine)-containing medicinal legume. We additionally investigated the cross nodulation, infection pattern, light and electron microscopies of root nodule sections of S. flavescens infected by various rhizobia. Seventeen genospecies of rhizobia belonging to five genera with seven types of symbiotic nodC genes were found to nodulate S. flavescens in natural soils. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 60 publications
3
28
0
Order By: Relevance
“…The results revealed that the studied strains nodulated only C. arietinum and no cross-nodulation compatibility was observed between chickpea nodule rhizobia and other mesorhizobia leguminous plants. Thiswas in congruence with previous reports of cross nodulation tests [31,64]. Biofilm formation ability of all 54 tested strains can be considered as the key factor for symbiotic efficiency and it supports the possibility for their commercial use in stress condition [65].…”
Section: Discussionsupporting
confidence: 91%
“…The results revealed that the studied strains nodulated only C. arietinum and no cross-nodulation compatibility was observed between chickpea nodule rhizobia and other mesorhizobia leguminous plants. Thiswas in congruence with previous reports of cross nodulation tests [31,64]. Biofilm formation ability of all 54 tested strains can be considered as the key factor for symbiotic efficiency and it supports the possibility for their commercial use in stress condition [65].…”
Section: Discussionsupporting
confidence: 91%
“…These results enlarged the host spectrum of R. anhuiense, originally reported for rhizobia isolated from effective nodules of Vicia faba and Pisum sativum [31], and revealed relatively low species richness in beach pea rhizobia compared with those detected in soybean, common bean and Sophora flavescens, etc. [3,5,11,32].…”
Section: Discussionmentioning
confidence: 99%
“…However, the reports that Sophora alopecuroides and Sophora flavescens sampled in China are nodulated by Ensifer , Mesorhizobium , Phyllobacterium and Rhizobium with a wide range of symbiosis gene sequences [207,208] contrasts with the finding that New Zealand (NZ) native Sophora spp. were exclusively nodulated by Mesorhizobium spp.…”
Section: Papilionoideae-rhizobia Symbiosesmentioning
confidence: 99%